Complete Neurological Recovery Following 360-Degree Decompression and Fusion for T11 Giant Cell Tumor: A Case Report - Ermawan, Rieva; Bayu Sakti Jiwandono; Denny Firdaus (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Giant cell tumors (GCTs) are benign but locally aggressive bone tumors that rarely affect the spine. The thoracic spine is an even rarer location for GCTs, and their presentation with paraplegia poses a significant challenge. This case report describes the successful surgical management of a T11 GCT-causing paraplegia, highlighting the importance of early diagnosis and aggressive surgical intervention. Case presentation: A 27-year-old female presented with acute paraplegia and a history of chronic lower back pain. Imaging revealed a destructive lesion in the T11 vertebral body with spinal cord compression. The patient underwent a 360-degree decompression, en bloc tumor resection, and posterior spinal fusion. Histopathological analysis confirmed the diagnosis of GCT. The patient experienced complete neurological recovery within five days postoperatively and remained symptom-free at the 5-year follow-up. Conclusion: This case demonstrates the feasibility of achieving complete neurological recovery in patients with T11 GCT and paraplegia through aggressive surgical intervention. Early diagnosis and complete tumor resection followed by spinal stabilization are crucial for optimal outcomes.